Ethnicity and refractive errors in Peruvian children aged 7–11 years: A five-year analysis of the Demographic and Health Survey - De-La-Borda-Prazak, Guillermo (2024)
Objective: To assess the association between ethnicity and self-reported refractive errors (REs) among Peruvian children aged 7–11 years. Materials and methods: We conducted a cross-sectional study incorporating a secondary data analysis of 2017–2021 data from the Peruvian Demographic and Health Survey (DHS). REs and ethnicity were obtained from focal child's mother's report. Four outcomes were assessed: hyperopia, myopia, astigmatism and any RE. We included potential confounders, such as age, sex, wealth index, area of residence, region of origin, frequency of watching TV and watching screens at less than 30 cm distance. Generalised linear models with the Poisson family and log link function were used to calculate crude prevalence ratio and adjusted prevalence ratio (aPR) with 95% confidence intervals (95% CI). Results: Data from a total of 52,753 children were included. The prevalence of RE in children aged 7–11 years was 10.90% (95% CI 10.49–11.33), of which 5.19% were hyperopia, 3.35% myopia and 2.36% astigmatism. Those of the Aymara ethnicity were less likely to suffer from any RE and astigmatism (aPR = 0.68, 95% CI 0.46–0.99, p = 0.046; aPR = 0.70, 95% CI 0.53–0.92, p = 0.012, respectively), Members of Amazon groups were more likely to have hyperopia (aPR = 1.95, 95% CI 1.14–3.36, p = 0.015) and Quechuas were more likely to have myopia (aPR =1.29, 95% CI 1.02–1.62, p = 0.028), where all were compared to Mestizos. Conclusion: About 1 in 10 Peruvian children suffer from a RE. The most frequent RE in this study was hyperopia. Ethnic differences were seen in the frequency of RE.